Analysis of the Intestinal Flora in Male Versus Female Swamp Eels (Monopterus albus) - Wang, Ying; Zhang, Jinhua; Zhou, Qiubai; Wang, Zirui; Gao, Miao; Yang, Xin; Liu, Yu; Zhang, Zhengzhou; Jiang, Wenhao; Hu, Chonghua; Zhang, Wenping (Frontiers in Microbiology, 2020)
The purpose of this study is to investigate the effect of intestinal flora in the sex reversal of swamp eel. The difference of intestinal flora between female swamp eel and male swamp eel was studied by using the same parent swamp eels as materials. Under the condition of consistent age, environment, diet, and other conditions, 18 healthy swamp eels (half male and half female) with the same size (39.4±2.3g) were selected after one year of breeding. Intestinal of each 3 swamps eel were mixed in a sample according to their sex and labeled as follows: FM1-FM3 (n=3) for females and MM1-MM3 (n=3) for males. Intestinal flora was characterized by High-throughput Sequencing. The results showed that there were significant differences from the composition, structure, and diversity of the intestinal flora of swamp eel. At the Phylum level, the relative abundance of Actinobacteria and Spirochaetes in female swamp eel was significantly higher (P < 0.05) than that in males swamp eel. The relative abundance of Mycobacterium, Bacillus, and Vagococcus in female swamp eel was considerably higher (P < 0.05) than that in males swamp eel at the genus level. The Alpha diversity of females was higher than that of males, and the Shannon index of females was significantly higher (P<0.05, Tukey's HSD) than that in males. Beta diversity, including NMDS ordination, UPGMA cluster analysis, and PLS-DA analysis results showed that female swamp eel and male swamp eel could be distinguished and grouped into two groups, and there were significant differences in intestinal flora between the two groups. The LEfSe analysis results showed that the dominant bacteria of male swamp eel were Cetobacterium, while female swamp eel was Clostridium_sp_ND2, Mycobacterium, Alphaproteobacteria, and Bacilli. These dominant bacteria may have some effect on the sex reversal of swamp eels.